Assessment of Problem-Based Learning (PBL): Poster Presentation as a Tool of Assessment - Rano Mal Piryani; Suneel Piryani; Nudrat Zeba; Aamir Hussain (Universitas Pendidikan Ganesha, 2022)
Assessment is considered the single most significant determinant of learning that influences student learning behavior broadly. However, assessment in the context of PBL requires a constructive alignment between PBL objectives and assessment, which can be achieved through an integrative assessment approach. This study aimed to assess the performance of groups of students participating in PBL for poster preparation and presentation on criteria-referenced. This type of research is descriptive research. The methods used in collecting data are observation and questionnaires. The instrument used in this research is a questionnaire. The techniques used to analyze the data are descriptive, qualitative, and quantitative. The study results were that half of the students scored less than 50% in designing posters on the